2021
DOI: 10.1038/s41419-021-04323-1
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of KAT2A on cGAS-related immunity in inflammation amplification of systemic lupus erythematosus

Abstract: Previous studies demonstrated that cGAS pathway is related to the inflammation amplification in a variety of autoimmune diseases. Lysine acetyltransferase family (KATs) can regulate the nuclear transcription or cytoplasmic activation of cGAS through different mechanisms. However, its role and related immunity patterns in systemic lupus erythematosus (SLE) have not been explored. In this study, RNA-seq and scRNA-seq profiling were performed for peripheral blood mononuclear cells (PBMCs) from patients with SLE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A recent work found that in systemic lupus erythematosus (SLE), KAT2A was abnormally upregulated, and modulated the expression and acetylation of cyclic GMP‐AMP synthase. 48 Clinical data identified that NLRP3 was hyperactivated in macrophages of SLE patients and its dysregulation was positively correlated with SLE disease activity index. 49 In this way, the enhanced inflammasome activation by KAT2A might also contribute to the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work found that in systemic lupus erythematosus (SLE), KAT2A was abnormally upregulated, and modulated the expression and acetylation of cyclic GMP‐AMP synthase. 48 Clinical data identified that NLRP3 was hyperactivated in macrophages of SLE patients and its dysregulation was positively correlated with SLE disease activity index. 49 In this way, the enhanced inflammasome activation by KAT2A might also contribute to the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…reported that in IL‐1β‐treated HepG2 cells, KAT2A bound to the promoter of IL‐1β‐responsive genes for mediating the transcription activation via H3K9ac, indicating KAT2A might be also indispensable for IL‐1β downstream and effectors. A recent work found that in systemic lupus erythematosus (SLE), KAT2A was abnormally upregulated, and modulated the expression and acetylation of cyclic GMP‐AMP synthase 48 . Clinical data identified that NLRP3 was hyperactivated in macrophages of SLE patients and its dysregulation was positively correlated with SLE disease activity index 49 .…”
Section: Discussionmentioning
confidence: 99%
“…KAT2A histone acetyltransferase is a transcriptional activator, but it can also repress NK-κB through ubiquitination of its RELA subunit. KAT2A has been reported to promote carcinogenesis in colorectal cancer by interacting with RNA-binding protein PTBP1 [ 26 ] and to modulate cGAS through increasing expression and post-translational modification in systemic lupus erythematosus [ 27 ]. In addtrion, KAT2A-mediated histone succinylation was recently found to play a new role in the regulation of gene expression and β-catenin stability to promote tumor cell proliferation and invasion of pancreatic carcinoma cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%